The influence of Russian folk Art on Avant-Garde artists - Svishchenko, Kseniia (2017)
In this internship report, I will describe my experience at the Collection of the Russian Museum in Malaga, Spain. It is the first European branch of the State Russian Museum in Saint Petersburg. The aim of this internship report is to comment on my experience at the Education Department of the museum in question as well as to study several works of the Russian avant-garde artists exhibited at the museum during my internship.